High risk pregnancy associated perinatal morbidity and mortality: a second birth population-based survey in Huai'an in 2015 - Xiaoqin Zhu; Huiyuan Niu; Hui Wang; Xiaoqiong Li; Tingting Qi; Weijie Ding; Liangrong Han; Muling Zhang; Honghua Guan; Shouzhong Li; Chunhong Tang; Yaodong Yin; et al. (BMC, 2019)
Abstract Background The objective of this survey was to explore the association between pregnancy complications and perinatal outcome from regionally total birth population. Methods In this prospectively collected data of complete birth registries from all level I-III hospitals in Huai'an in 2015, perinatal morbidity and mortality in relation to pregnancy complications and perinatal outcome were analyzed using international definitions. The results were compared with that of 2010 survey in the same region. Results Of 59,424 total births in the hospitals of level I (n = 85), II (16) and III (6), delivery rate was 30.4, 40.1 and 29.5%, and rates of pregnancy complications were 12.9, 9.8 and 21.1% (average 14.1%), with antenatal corticosteroids rate in < 37 gestational weeks being 17.3, 31.0 and 39.9% (mean 36.6%), respectively. The preterm birth rate was 0.6, 2.7 and 9.5% (mean 4.06%), and the composite rate of fetal death, stillbirth, and death immediately after delivery was 0.1, 0.4 and 0.6%, respectively. By multivariable logistic regression analysis, congenital anomalies, low Apgar scores, multi-pregnancy and amniotic fluid contamination were risk factors of adverse perinatal outcomes. Despite a higher rate of pregnancy complications than in 2010 survey, perinatal and neonatal mortality continued to fall, in particular in very preterm births. The high cesarean delivery rate in non-medically indicated cases remained a challenge. Conclusions Our regional birth-population data in 2015 revealed a robust and persistent improvement in the perinatal care and management of high risk pregnancies and deliveries, which should enable more studies using similar concept and protocol for vital statistics to verify the reliability and feasibility.